PENGARUH SIKLUS HIDUP PERUSAHAAN TERHADAP MANAJEMEN LABA DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MEDIASI - SETIAWAN, ARDINATA; , HARIYATI (Jurnal Akuntansi AKUNESA, 2018)
The objective of this study is to specify the effect of company life cycle on earning management mediated by corporate governance. The sample in this study are 87 companies that registered on the Indonesia Stock Exchange (BEI) from 2015-2017. The data analysis technique applied in this study is simple and multiple linear regression analysis applying SPSS 21. The outcomes in this study indicated that the company life cycle has a negative effect on earning management, the company life cycle has a negative effect on corporate governance, corporate governance has no effect on earning management, and corporate governance cannot mediate the effect of company life cycle on earning management.Keyword: Company Life Cycle, Corporate Governance, Earning Management